(untitled) (Dandao Xuebao/Journal of Ballistics, 2023)
In order to study the feasibility of latent weapon safely landing underwater by using parachute and separating into parts, the mathematic models were established on the basis of the analysis of the whole motion process including the deceleration and the weapon landing. The characteristics of the deceleration motion were numerically simulated. The simulation results of the motion of weapon and bay section in the process of weapon decelerating until landing were obtained. The effect of the parachute opening angle on the whole landing process was analyzed. The simulation result shows that this scheme is feasible for the weapon safely landing by choosing the appropriate parameters such as opening angle of parachute, the opening depth, the separation depth of bay section and the length of steel cable.